A novel configuration of a traditional rapid response team decreases non–intensive care unit arrests and overall hospital mortality. Issue 6 (16th March 2015) - Davis, Daniel P.; Aguilar, Steve A.; Graham, Patricia G.; Lawrence, Brenna; Sell, Rebecca E.; Minokadeh, Anushirvan; Husa, Ruchika D.
<x xml:space="preserve">Abstract</x> BACKGROUND In‐hospital cardiopulmonary arrest (CPA) accounts for substantial morbidity and mortality. Rapid response teams (RRTs) are designed to prevent non–intensive care unit (ICU) CPA through early detection and intervention. However, existing evidence has not consistently demonstrated a clear benefit. OBJECTIVE To explore the effectiveness of a novel RRT program design to decrease non‐ICU CPA and overall hospital mortality. METHODS This study was conducted from the start of fiscal year 2005 to 2011. In November 2007, our hospitals implemented RRTs as part of a novel resuscitation program. Charge nurses from each inpatient unit underwent training as unit‐specific RRT members. Additionally, all inpatient staff received annual training in RRT concepts including surveillance and recognition of deterioration. We compared the incidence of ICU and non‐ICU CPA from first complete preimplementation year 2006 to postimplementation years 2007 to 2011. Overall hospital mortality was also reported. RESULTS The incidence of non‐ICU CPA decreased, whereas the incidence of ICU CPA remained unchanged. Overall hospital mortality also decreased (2.12% to 1.74%, P < 0.001). The year‐over‐year change in RRT activations was inversely related to the change in Code Blue activations for each inpatient unit (r = −0.68, P < 0.001). CONCLUSION Our novel RRT program was associated with a decreased incidence of non‐ICU CPA and improved hospital mortality. Journal of Hospital Medicine 2015;10:352–357. © 2015 Society of Hospital Medicine